Patches of synchronized activity in the cerebellar cortex evoked by mossy-fiber stimulation: Questioning the role of parallel fibers - Cohen, Dana (The National Academy of Sciences, 1998)
The discrepancy between the structural longitudinal organization of the parallel-fiber system in the cerebellar cortex and the functional mosaic-like organization of the cortex has provoked controversial theories about the flow of information in the cerebellum. We address this issue by characterizing the spatiotemporal organization of neuronal activity in the cerebellar cortex by using optical imaging of voltage-sensitive dyes in isolated guinea-pig cerebellum. Parallel-fiber stimulation evoked a narrow beam of activity, which propagated along the parallel fibers. Stimulation of the mossy fibers elicited a circular, nonpropagating patch of synchronized activity. These results strongly support the hypothesis that a beam of parallel fibers, activated by a focal group of granule cells, fails to activate the Purkinje cells along most of its length. It is thus the ascending axon of the granule cell, and not its parallel branches, that activates and defines the basic functional modules of the cerebellar cortex.